2022
DOI: 10.3390/bios12121140
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Ultrasensitive Sensing of Uric Acid on Non-Enzymatic Porous Cobalt Oxide Nanosheets-Based Sensor

Abstract: Transition metal oxide (TMO)-based nanomaterials are effectively utilized to fabricate clinically useful ultra-sensitive sensors. Different nanostructured nanomaterials of TMO have attracted a lot of interest from researchers for diverse applications. Herein, we utilized a hydrothermal method to develop porous nanosheets of cobalt oxide. This synthesis method is simple and low temperature-based. The morphology of the porous nanosheets like cobalt oxide was investigated in detail using FESEM and TEM. The morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Figure 5 a depicts the CV response curve of the cobalt oxide puffy balls/GC sensor for 0 mM and 25 mM UA concentrations. A sharp increase in current response is seen in the presence of UA due to the UA oxidation, where the p-type nature of the cobalt oxide semiconductor plays a crucial role in swift electron transfer to the electrode surface by providing excess hole concentration [ 30 , 36 , 37 ]. A detailed UA sensing mechanism over cobalt oxide is proposed by Hu et al [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 5 a depicts the CV response curve of the cobalt oxide puffy balls/GC sensor for 0 mM and 25 mM UA concentrations. A sharp increase in current response is seen in the presence of UA due to the UA oxidation, where the p-type nature of the cobalt oxide semiconductor plays a crucial role in swift electron transfer to the electrode surface by providing excess hole concentration [ 30 , 36 , 37 ]. A detailed UA sensing mechanism over cobalt oxide is proposed by Hu et al [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The electrochemical analysis was performed using EIS, CV, and DPV measurements. We utilized the previously optimized cobalt oxide amount and pH to get the optimum sensing response of the fabricated sensor [ 36 , 37 , 38 ]. The CV was performed in a 5 mM probe solution of potassium hexacyanoferrate (purity ≥ 9 9%, K 3 [Fe(CN) 6 ]) in 0.1 M KCl under varying scan rates from 10 mVs −1 to 200 mVs −1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 In addition, it was also reported that the p-type nature of the cobalt oxide nanostructure provided excess holes (charge carriers) which resulted in the easy capture of electrons from the oxidation of UA. 33…”
Section: Resultsmentioning
confidence: 99%
“…29 In addition, it was also reported that the p-type nature of the cobalt oxide nanostructure provided excess holes (charge carriers) which resulted in the easy capture of electrons from the oxidation of UA. 33 Next, the CV response curves were measured in various UA concentrations (5-400 mM) in PBS buffer at a 50 mV s À1 scan rate (Fig. 7b).…”
Section: Ua Detectionmentioning
confidence: 99%